(untitled) (World Economics and Finance Bulletin, 2024)
The role and importance of small business in the development of the economy is highlighted in the article. In addition, the advantages and weaknesses of small business are discussed. It should also be noted that small business does not develop separately. Various factors influence its development, and small business must take them into account.